94.2k views
5 votes
What is the solution for the following equation? 6(x + 5) + 2 = 8(2x - 5) + 22

User MemphiZ
by
6.0k points

2 Answers

6 votes

Answer:

x=5

Explanation:

6(x + 5) + 2 = 8(2x - 5) + 22

6x+30+2=16x-40+22

6x+32=16x-18

6x-16x= -18-32

-10x= -50

x= -50/-10

x=5

User Joe Kirk
by
6.6k points
6 votes

Answer:

x = 5

Explanation:

6(x + 5) + 2 = 8(2x - 5) + 22

6x + 30 + 2 = 16x - 40 + 22

6x + 32 = 16x - 18

6x = 16x - 50

-10x = -50

x = 5

Best of Luck!

User Farhan Jatt
by
6.1k points